3D SCAFFOLDS BY 3D BIOPRINTING - GADAKH, ARCHANA SHANTARAM; KULKARNI, ABHIJEET DATTATRAYA (International Journal of Current Pharmaceutical Research, 2023)
When it comes to tissue engineering, 3D printing is a crucial technique for creating intricate constructions using biocompatible materials, cells, and supporting elements. The concept of "3D bioprinting" is concerning 3D printing, which may be used to design personalised implants, paving the way for new bio-manufacturing methods. The method of 3D bioprinting is promising because it can create biomimetic 3D structures that mimic the extracellular matrix and build extremely accurate multifunctional scaffolds with uniform cell distribution for tissue repair and regeneration. The focus of this review is on the 3D printed constructions made from various synthetic and natural materials. With an emphasis on the most recent developments, this study aims to provide an overview of the state-of-the-art field of 3D printing techniques in applications for tissue engineering. An evaluation and overview of using 3D bioprinting, viewpoints of bio-ink, printing technology, and application are presented in this review.